Outcome of primary trabeculotomy ab interno (Trabectome) surgery in patients with steroid-induced glaucoma. Issue 50 (December 2016) - Ngai, Philip; Kim, Grace; Chak, Garrick; Lin, Ken; Maeda, Masahiro; Mosaed, Sameh
Abstract : Abstract: To determine the efficacy and safety of Trabectome surgery on patients with steroid response, ranging from ocular hypertension refractory to maximal medical therapy to the development of steroid-induced glaucoma. A nonrandomized, nonblinded, retrospective study of 20 subjects with steroid response was conducted. All 20 eyes underwent Trabectome surgery alone. Nine subjects had steroid response with unremarkable visual field, 3 had mild steroid-induced glaucoma, and 8 had advanced steroid-induced glaucoma. Outcome measures included intraocular pressure (IOP), number of glaucoma medications, need for secondary glaucoma surgery, and steroid regimen. Mann–Whitney U test was used to compare postoperative IOP and number of medications to preoperative IOP and number of medications. Kaplan–Meier was used for survival analysis, and success was defined as: IOP reduced by 20% or more on any 2 consecutive visits after 3 months; IOP ⩽21 mm Hg on any 2 consecutive visits after 3 months; and no secondary glaucoma surgery. The average preoperative IOP was 33.8 ± 6.9 mm Hg and average preoperative glaucoma medication usage was 3.85 ± 0.75 medications. At 12 months, the IOP was reduced to 15.00 ± 3.46 mm Hg ( P = 0.03) and glaucoma medication was reduced to 2.3 ± 1.4 ( P < 0.01). The survival rate at 12 months was 93%. At 12 months, 10 patients were continued on their preoperative steroid treatments, 5 were on tapered steroid treatments, and 5 had ceased steroid treatments entirely. One patient required secondary glaucoma surgery (glaucoma drainage device). No other complications were noted. The Trabectome procedure is safe and highly effective for steroid-response glaucoma, even in the context of continued steroid treatment.